Study of relation among accelerometer of physical activity and different context factors in primary schools in Iraq - kalttan, Muhanad abed (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to examine the relationship between various context factors in elementary physical education with accelerometer measurements of physical activity. During 2019–2020, there were data collected from 285 students from a private school in Baghdad (1st to 5th grade, 135 males, 135females). In multi-level models, key effects and interactions between the factors were investigated. Statistically significant was a bidirectional interaction between the learning context and the size of class for percent. In comparison with motor skill lessons in larger classes, the biggest differences were between fitness lessons using small classes.